Allergies and Asthma: Employing principles of social justice as a guide in public health policy development - Behrmann, Jason (Les ateliers de l'éthique / The Ethics Forum, 2010)
The growing epidemic of allergy and allergy-induced asthma poses a significant challenge to population health. This article, written for a target audience of policy-makers in public health, aims to contribute to the development of policies to counter allergy morbidities by demonstrating how principles of social justice can guide public health initiatives in reducing allergy and asthma triggers. Following a discussion of why theories of social justice have utility in analyzing allergy, a step-wise policy assessment protocol formulated on Rawlsian principles of social justice is presented. This protocol can serve as a tool to aid in prioritizing public health initiatives and identifying ethically problematic policies that necessitate reform. Criteria for policy assessment include: 1) whether a tentative public health intervention would provide equal health benefit to a range of allergy and asthma sufferers, 2) whether targeting initiatives towards particular societal groups is merited based on the notion of ‘worst-off status’ of certain population segments, and 3) whether targeted policies have the potential for stigmatization. The article concludes by analyzing three examples of policies used in reducing allergy and asthma triggers in order to convey the general thought process underlying the use of the assessment protocol, which public health officials could replicate as a guide in actual, region-specific policy development.